Mobile JKN as an Application to Improve Service Quality of Social Security Administration Agency for Health in Hemodialysis Unit - Manalu, Obed Andy F.; Girsang, Ermi; Nasution, Ali Napiah (FORIKES, 2025)
Digital transformation in healthcare services is a major focus of BPJS Kesehatan (Social Security Administration Agency for Health) through the Mobile JKN application. This study aimed to evaluate the quality of BPJS services using Mobile JKN in the Hemodialysis Unit of Dr. Pirngadi Regional General Hospital in Medan, using a mixed methods approach (quantitative and qualitative). The quantitative method was conducted by distributing questionnaires to 109 patients who use Mobile JKN. The results showed that the aspect of ease of access scored an average of 3.72, service speed 4.0, application features 3.35, and patient satisfaction 3.77. These findings indicate that the majority of patients feel helped by the existence of Mobile JKN, especially in terms of queue efficiency and ease of administration. However, there are still obstacles such as limited digital literacy, technical difficulties in logging in, and low utilization of additional features such as changing health facilities and online consultations. In-depth interviews supported the quantitative data, in which most elderly respondents experienced difficulties in using the application without assistance. BPJS Kesehatan officers and medical personnel play an important role in assisting the application usage process. It can be concluded that Mobile JKN has significantly improved BPJS Kesehatan services, but optimizing its utilization still requires improvements in education and assistance as well as technical system improvements.Keywords: digital health services; hemodialysis unit; service quality